2012
DOI: 10.6061/clinics/2012(05)15
|View full text |Cite
|
Sign up to set email alerts
|

Acute and subchronic toxicological evaluation of Echinophora platyloba DC (Apiaceae) total extract in Wistar rats

Abstract: OBJECTIVE:Echinophora platyloba DC is a widely used herbal medicine and food seasoning in Iran. It is claimed to exert antimicrobial, antifungal, and antispasmodic effects. Despite the prevalent use of this plant as a food and medicine, there are no reports on its possible toxic effects. To evaluate the safety of E. platyloba, we tested its acute and sub-chronic toxicity in male and female Wistar rats.METHODS:Rats were orally treated with four different single doses of E. platyloba total extract and screened f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 10 publications
(8 reference statements)
0
10
0
Order By: Relevance
“…This plant with the local name Fedaleh is used as a seasoning in food, and local people use this in pickle and tomato sauce as preservatives, antifungal, and antimicrobial. [ 4 5 ]…”
Section: Biological Effects Of Echinophora Genusmentioning
confidence: 99%
See 2 more Smart Citations
“…This plant with the local name Fedaleh is used as a seasoning in food, and local people use this in pickle and tomato sauce as preservatives, antifungal, and antimicrobial. [ 4 5 ]…”
Section: Biological Effects Of Echinophora Genusmentioning
confidence: 99%
“…Acute and chronic toxicity effects of the extract have been investigated by Mirghazanfari et al ., where the results show that Echinophora extract at a dose of 50–200 mg/kg is safe and a dose of 500 mg/kg of Wistar rats body weight is toxic. [ 4 ] Finally, studying the extracts and essential oil of this plant showed that the extract has antispasmodic effect to stimulate muscle contraction and bowel. [ 66 ]…”
Section: Biological Effects Of Echinophora Genusmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] Taking into consideration, the potent antifungal and antibacterial activity suggested that the methanolic extract of Echinophora platyloba DC could be a potentialcandidate as a cytotoxic and growth inhibitory agent. [10,11] The present study was undertaken to evaluate the antimutagenicity and cytotoxicity effects of crude methanolic extract of E. platyloba in Salmonella typhimurium (TA100) and malignant cell line in vitro respectively. Ames test is one of the most current test to assay anticancer and antimutagenesis effects using bacteria with special mutants [3].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical signs exhibited by the mice were observed prior to dosing at 1, 2, 3, 4, 5, 6, 7, and 8 hours post-dosing and daily thereafter for 14 days. Animals were observed for general behavioral change, body weigh change, and mortality for a period of 14 days post treatment (16). The number of dead animals in each group at the end of the study was expressed as percentage.…”
Section: Acute Toxicity Study In Micementioning
confidence: 99%